2011
DOI: 10.1111/j.1742-4658.2011.08227.x
|View full text |Cite
|
Sign up to set email alerts
|

PRDM1/Blimp1 downregulates expression of germinal center genes LMO2 and HGAL

Abstract: Human germinal center–associated lymphoma (HGAL) and LIM domain only-2 (LMO2) are proteins highly expressed in germinal center (GC) B lymphocytes. HGAL and LMO2 are also expressed in GC-derived lymphomas and distinguish biologically distinct subgroups of diffuse large B-cell lymphomas (DLBCL) associated with improved survival. However, little is known about their regulation. PRDM1/Blimp-1 is a master regulator of terminal B cell differentiation and may also function as a tumor suppressor in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…Our lab and others have previously demonstrated that PRDM1 directly suppresses components of activated B cells, suggesting that PRDM1 might have a key role in regulating ELL family expression (47, 52, 53). In Figures 1A, 2B and Figure 1C, the expression of PRDM1 is shown to coincide with loss of ELL3 expression.…”
Section: Resultsmentioning
confidence: 79%
“…Our lab and others have previously demonstrated that PRDM1 directly suppresses components of activated B cells, suggesting that PRDM1 might have a key role in regulating ELL family expression (47, 52, 53). In Figures 1A, 2B and Figure 1C, the expression of PRDM1 is shown to coincide with loss of ELL3 expression.…”
Section: Resultsmentioning
confidence: 79%
“…8 B-cell receptor 29,30 and/or NFB activation 32 during GC lymphocyte differentiation process can up-regulate miR-155 and PRDM1 expression leading to decreased HGAL protein expression, increasing lymphocyte motility and potentially affecting egress from GC. As shown herein and in our previous work, both miR-155 and PRDM1 directly regulate HGAL expression, 8 and overexpression of PRDM1 in DLBCL cell lines is not increasing miR-155 expression (data not shown). Overall, our current observations extend our previous findings on HGAL regulation by the PRDM1 8 and identify a novel role of miR-155 in immune system.…”
Section: Discussionmentioning
confidence: 84%
“…As shown herein and in our previous work, both miR-155 and PRDM1 directly regulate HGAL expression, 8 and overexpression of PRDM1 in DLBCL cell lines is not increasing miR-155 expression (data not shown). Overall, our current observations extend our previous findings on HGAL regulation by the PRDM1 8 and identify a novel role of miR-155 in immune system. miR-155 is also implicated in pathogenesis of lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations